Development of Multimedia-Based and Islamic English Textbooks at IAIN Palopo Language Laboratory - Riawarda M, Andi; Yahya, Amalia (Institut Agama Islam Negeri Palopo, 2023)
The purpose of this research is to develop multimedia-based English teaching materials for the language lab, integrating basic Islamic values to meet students' needs at IAIN Palopo. The goal is to ensure the teaching materials are valid, practical, and effective in enhancing English competence while reinforcing Islamic knowledge. This study investigates the profile of such English teaching materials, evaluating their validity, practicality, and effectiveness in the language lab with a multimedia system. The research employs the Research and Development (R&D) method using the modified ADDIE design model: Analyze, Design, Develop, Implement, Evaluate, simplified into six processes: Needs analysis, material development, expert validation, product revision, product trial, and final product. Based on needs analysis through questionnaires and interviews, the developed teaching materials support language lab learning and consist of six units: (1) Pillars of Islam, (2) The First Pillar: Shahada, (3) The Second Pillar: Prayer, (4) The Third Pillar: Zakat, (5) The Fourth Pillar: Fasting, (6) The Fifth Pillar: Hajj. Each unit follows a structured framework based on student needs. Students engage in activities like Puzzling, Rearranging, Matching, and Ordering, using multimedia elements such as images and text, and utilizing WhatsApp on mobile phones. This approach strengthens students' English and Islamic vocabulary, providing a foundation before core material. This study aims to support IAIN Palopo students by integrating Islamic content in English learning, enhancing both linguistic and religious understanding through innovative, multimedia teaching materials.